Enhancing Human Knowledge and Capabilities with Artificial Intelligence Tools for Education - Jackson, Emerson Abraham; Jackson, Hudson F. (Educational Challenges, 2024)
This study explores the different ways Artificial Intelligence (AI) tools bolster human knowledge and boost intellectual and creative efforts within the educational sector. It provides a broad examination of AI's potential to enhance educational processes and outcomes while also assessing the ramifications of AI-driven creative destruction on the job market encompassing both job displacement and the emerging scope for new knowledge creation. Purpose. The study aims to explore the different ways in which AI tools enhance human knowledge and capabilities and their role in augmenting human intellectual and creative endeavours in education. By examining how AI can improve educational processes and outcomes, it highlights the potential for significant advancements. Additionally, the study critically examines the implications of AI-driven creative destruction on the job market, focusing on the education sector. This includes understanding both job displacement and the creation of new opportunities that require advanced skills. Methods. This research involves a detailed analysis of various AI applications across the education domain. It employs virtual interviews with students and educators to provide detailed examples of AI's impact and reviews existing literature to contextualise these findings within broader economic implications. By focusing on the education sector, the study provides a comprehensive overview of how AI is being implemented and the outcomes of these implementations. This approach allows for a thorough understanding of both the benefits and challenges connected with AI integration. Results. The study suggests that AI significantly improves data processing capabilities, leading to notable advancements in educational research and personalised learning. These improvements can facilitate decision-making and innovation. However, AI also disrupts traditional employment patterns, displacing routine jobs that are easily automated. Conversely, it creates new roles that demand advanced technical skills and continuous education, highlighting a shift in the job market toward more specialised and high-skill positions. Conclusion. While AI can present substantial benefits in terms of efficiency and innovation, it poses significant challenges in the form of job displacement. To manage these transitions effectively, strategic responses from policymakers and educational institutions are essential. These strategies should aim to ensure equitable access to AI’s benefits and support workforce adaptation. By fostering a balanced integration of technological advancements and human well-being, it is possible to mitigate the negative impacts while maximising the positive outcomes of AI.